2020
DOI: 10.3390/separations7010018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Varronia curassavica Jacq. Terpenoids by Flow Modulated Two-Dimensional Gas Chromatography Coupled to Mass Spectrometry

Abstract: In this study, a metabolomic approach was used to investigate the effect of seasonality on the chemical composition and yield of anti-inflammatory active principle, α-humulene, in the essential oil of three genotypes of Varronia curassavica Jacq. (Syn. Cordia verbenaceae). The essential oils were extracted by hydrodistillation and analyzed by comprehensive two-dimensional gas chromatography coupled to mass spectrometry (GC×GC-MS). The GC×GC approach a three-fold improvement in qualitative analysis (48 compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 64 publications
0
15
0
1
Order By: Relevance
“…A reproducible division of approximately 1:6 was achieved throughout the experiments. The interested reader is directed elsewhere for more details on the instrument setup [ 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reproducible division of approximately 1:6 was achieved throughout the experiments. The interested reader is directed elsewhere for more details on the instrument setup [ 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Analytical tools that provide high resolution and sensitivity for untargeted analysis of the plant metabolome are desperately needed. Among these tools, comprehensive two-dimensional gas chromatography coupled to mass spectrometry (GC×GC-MS) is characterized for the increased peak capacity [ 17 , 18 , 19 ], increasing the identification power of plants volatiles and semi-volatiles composition [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the detailed characterization of the V. curassavica essential oil, the active ingredient in the oil that is monitored by the pharmaceutical industry, α‐humulene, was quantified in the different oil samples. It was found that the concentration of this compound is influenced by both the genotype as well as the harvest season 77 …”
Section: Trends In the Chromatographic Analysis Of Volatile Flavor Anmentioning
confidence: 99%
“…This technique combines two sequential separations by exploring complementary solvation properties, signicantly enhancing the peak capacity of the composite system. 1,2 For instance, GC Â GC separations have been successfully applied to metabolomics, [3][4][5] food analysis, [6][7][8] and petroleomics [9][10][11][12] where analyte discovery and identication beneted from the improved chromatographic resolution. Also, the enhanced peak capacity of GC Â GC enables simplication of sample preparation methods, 13 which is interesting for non-targeted analyses with limited sample availability or scouting studies.…”
Section: Introductionmentioning
confidence: 99%